Introduction to Assessment in Medical Education (First of the Series) - Mustafa Kemal Alimoğlu (Journal of Medical Education and Family Medicine)
AbstractThis paper includes an operating definition of the assessment and further explanations of each unit of the definition. Some assessment principles and practical examples for undergraduate medical education are provided.